The Histological Studies of Parathyroid’ Gland in Laying White Leghorn Hens (Gallus domesticus) in Relation to the Serum Calcium Level - Joshi, Sanjeev; Singh, Kalyan; Ghosal, A K (Annals of Arid Zone, 2016)
The parenchymal cells recorded were dark chief, 21.33%; intermediate, 73.46% and light chief, 5.20% and their dimensions (in microns) were, 17.30 ± 4.49, 19.98 ± 4.15 and 850 ± 8.49, respectively, and mean of serum calcium was 49.66 mg/100 ml.